No genetic causal association between iron status and osteoporosis: A two-sample Mendelian randomization - Xu, Jiawen; Ma, Jun; Chen, Jialei; Zhang, Shaoyun; Zheng, Che; Si, Haibo; Wu, Yuangang; Liu, Yuan; Li, Mingyang; Wu, Limin; Shen, Bin (Frontiers in Endocrinology, 2022)
Abstract Objective: To explore the genetic causal association between osteoporosis (OP) and iron status through Mendelian randomization (MR). Methods: Publicly available genome-wide association study (GWAS) summary data were used for MR analysis with four iron status-related indicators (ferritin, iron, total iron binding capacity, and transferrin saturation) as exposures and three different types of OP (OP, OP with pathological fracture, and postmenopausal OP with pathological fracture) as outcomes. The inverse-variance weighted (IVW) method was used to analyse the genetic causal association between the four indicators of iron status and OP. The heterogeneity of MR results was determined using IVW and MR‒Egger methods. The pleiotropy of MR results was determined using MR‒Egger regression. A leave-one-SNP-out test was performed to determine whether the MR results were affected by a single nucleotide polymorphism (SNP). The weighted median method was conducted to further validate our results. Results: Based on IVW, MR‒Egger and weighted median models, we found no causal association between iron status (ferritin, iron, total iron binding capacity, or transferrin saturation) and OP (Pbeta > 0.05 in all models). IVW and MR‒Egger analysis of OP with pathological fracture and iron status indicators showed no potential genetic causal association (Pbeta＞ 0.05 in the two analyses). The results of the weighted median were consistent with those of IVW (Pbeta> 0.05 in all analyses). There was no potential genetic causal association between iron status and postmenopausal OP with pathological fracture based on serum iron (Pbeta＞0.05 in all models). No heterogeneity or horizontal pleiotropy was found in any of the analyses. None of the leave-one-out tests in the analyses found any SNP that could affect the results of MR. Conclusion: Our results demonstrate that there is no genetic causal association between OP and iron status, but the effects of other factors were not excluded. Keywords: Osteoporosis; Iron status; Causal association; Mendelian randomization